Influence of impurity on electronic transition in coherent-strained quantum dot - Dan'kiv, O.O.; Peleshchak, R.M. (Functional Materials, 2006)
The influence of impurity on energy breadth of an optical gap for quantum dot is studied within the framework of deformation potential model. It is established that with size increase of a quantum dot with an ionization donor dopant an optical gap diminishes. For smaller radiuses (R₀ ~ 40 Å ÷ 57 Å) energy breadth of the basic optical transition Е in quantum dots with donor dopants is greater, than in unblended ones. For the major sizes of quantum dots R₀ ≥ 58 Å the converse effect is observed.